A MPPT Strategy Based on Fuzzy Control for a Wind Energy Conversion System. (2016) - Yaakoubi, Ali El; Asselman, Adel; Djebli, A.; Aroudam, El Hassan
Abstract: In order to maximize the amount of energy produced from a wind turbine according to the wind speed fluctuations, the WECS needs a controller able of ensuring its operation mode around the OPP. In this paper, a MPPT strategy is proposed, to extract a maximum power from a variable speed wind turbine based on squirrel cage induction machine drive by using fuzzy logic control. The proposed strategy is based upon the monitoring and the judgment of the power - rotational speed characteristic in the aim to find the optimum rotational speed that corresponds to the optimal produced power. The simulation results in MATLAB/SIMULINK of the entire WECS demonstrate the ability of the MPPT-FLC to extract a maximum power from the wind.